Analysis of the Terms of Al-Jarh wa Al-Ta'dil - Samsudin, Samsudin; Engkos Kosasih; Dadah, Dadah (al-Afkar, Journal For Islamic Studies, 2025)
The analysis of the terms al-Jarh wa At-Ta'dil is an integral part of the study of hadith in the Islamic tradition. Al-Jarh wa At-Ta'dil is a critical method used to assess the reliability of the hadith rawi-rawi, with the aim of determining whether the hadith conveyed by them is acceptable or not. This research aims to explore the concepts, methodologies, and implications of al-Jarh wa At-Ta'dil in the context of Islamic science. This study reveals that al-Jarh wa At-Ta'dil is not just a rawi assessment, but also reflects the efforts of hadith scholars to maintain the integrity and authority of hadith as a source of law in Islam. Criteria such as honesty, intelligence, memory, and morality are the main focus in the assessment of rawi. The methodology used involves a careful analysis of the rabbi's life history, a critical approach to their statements, and comparisons with other sources. By understanding well the principles of al-Jarh wa At-Ta'dil, we can strengthen our understanding of the validity of hadith and ensure the continuity of the scientific heritage in the Islamic tradition.